Unfit for purpose: A situational analysis of abortion care and gender-based violence. Issue 5 (October 2022) - Mainey, Lydia; O'Mullan, Catherine; Reid-Searl, Kerry
Abstract: Problem: Timely access to comprehensive abortion care is fundamental to reproductive autonomy; however, factors such as geographical location, politics, and religious influences create obstacles to this goal and may have distressing consequences for people seeking abortions in the context of gender-based violence. Aim: To investigate the broader situational elements of the Australian healthcare environment that affect abortion care for victims of gender-based violence. Methodology: Situational Analysis was used to conduct this study. The lead author interviewed 18 clinicians about their experiences of providing abortion care in the context of gender-based violence. Transcripts were analysed using situational maps, identifying the human and non-human elements affecting clinical care. Findings: Participants believed that patients were " mostly uncatered for ." They described a workforce unprepared to provide abortion care, generally, and gender-based violence interventions more specifically. Clinicians found that their pro-life colleagues centred their own needs, and many revealed that the workplace environments placed clinicians' and patients' safety at risk. Discussion: While abortion is a safe and straightforward procedure, the interconnectedness of time sensitivity, stigma, shifting legal landscapes, and high rates of gender-based violence mean that it is probably more complex than the current work models plan for. A trauma-informed integrated approach that protects the safety and wellbeing of patients and staff is needed. Conclusion: Healthcare services should implement streamlined evidence-based and trauma-informed abortion pathways that take full advantage of nurses' and midwives' skills, knowledge, and potential. As a priority, healthcare services should also introduce security measures and protocols to keep staff and patients safe.